Optimasi penggunaan dan perawatan pada mesin unit Phonska IV untuk meningkatkan produksi pupuk pada PT. XYZ - Agustina, Endang; Sari, Rizqi Novita (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
PT XYZ is a company engaged in the production of fertilizers. With the monthly targets that must be met. The phonka IV unit has several categories of machines such as the Rotating category, the Instrument category, the Electrical category, each category has several problems with its components. So that it can reduce the production that must be achieved and financial losses due to Downtime. Therefore, Company XYZ must calculate to find out the most optimal time interval to reduce damage to each category of its machines. The method used to solve this problem is to use the FMEA and RCM methods with the help of excel and minitab software to facilitate data calculations. The results of data processing show that the total RPN obtained with a total of 470. After calculating the Company's interval. The Rotation category should be done every 31.61 hours, for the Instrument category it should be done every 2.81 hours, for the Electrical category it should be done every 2.83 hours. Then the Company can find out the planned schedule.